Characterization of third generation cephalosporin-resistant Escherichia coli clinical isolates from Ushuaia, Argentina - Gramundi, Ivan (2022)
Escherichia coli is one of the main human pathogens causing different hospital- and community-acquired infections. During the period from January 2013 to March 2015, 1.96% (32/1632) of E. coli isolates recovered at the Hospital Regional de Ushuaia, Tierra del Fuego province, were resistant to third-generation cephalosporins (TGCs). These isolates were resistant to cefotaxime (91%) and/or ceftazidime (28%). No resistance to carbapenems was detected. Twenty-six isolates were positive for blaCTX-M gene, grouped as CTX-M-1/15 (54%); CTX-M-9/14 (25%); CTX-M-2 (17%); and CTX-M-1/15 plus CTX-M-9/14 (4%). Five TGC-resistant strains were positive for blaCMY gene, while one strain harbored TEM-19 ESBL. Twelve isolates were identified as ST131 E. coli hyperepidemic clone, and one as ST69. Genome sequence analysis of seven blaCTX-M-15 E. coli selected isolates confirm the circulation of ST131, ST617 and ST405 international high-risk clones in the city of Ushuaia.